Socio-environmental diagnosis of community urban gardens in the General Pueyrredon district - Del Rio, Jaime; Cabral, Victoria Noelia; Sordini, María Victoria (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
In recent decades, conventional agriculture has increased crop yields but has been unable to guarantee food security for the population. Currently, the food crisis extends throughout the planet, while environmental problems derived from this agro-productive model are becoming stronger and progressively affecting the sustainability of this activity. At the regional level, the southeast of the Buenos Aires province is characterized by conventional agricultural production, with the General Pueyrredon district (PGP) being a faithful exponent of this type of productive activity. Thus, several local organizations and self-convened neighbors develop activities from a critical perspective of the conventional agricultural model. They carry out a movement of protest and action, with the particularity of intervening or carrying out urban gardens located within the urban limits, with agroecological characteristics. Establishing a physical and intellectual space for interaction between the community, whether neighborhood, educational, or directed at society in general. With the aim of developing a cultural exchange, based on dialogic and practical actions in the field. The peculiarities of these spaces motivated their inclusion as an object of study in my undergraduate thesis work in environmental management. A socio-environmental diagnosis was carried out that allowed identifying spaces of urban horticulture that function in a community manner within the PGP. This diagnosis revealed their current situation, their main limits, and potentialities. In addition, a characterization of the different projects was carried out, and they were geographically located. This facilitated an approach to the way in which the different experiences relate to the urban social dynamics of the territories where they are located.